An Initial Validation of the NASA TROPICS Pathfinder Microwave Radiometer Observations - Amelia Gagnon; Samantha N. Hasler; Juliana Chew; William J. Blackwell; R. Vincent Leslie; Michael DiLiberto; Kerri Cahoy (IEEE Journal of Selected Topics in Applied Earth Observations and Remote Sensing)
The NASA Time-Resolved Observations of Precipitation structure and storm Intensity with a Constellation of Smallsats (TROPICS) Pathfinder CubeSat was placed into a sun-synchronous orbit by a SpaceX Falcon 9 launch vehicle during the June 30, 2021 Transporter-2 rideshare mission. The Pathfinder satellite carries a microwave radiometer with 12 channels (spanning 90–205 GHz) that are sensitive to the precipitation, humidity, and temperature structure of Earth's atmosphere. In this work, we compare the TROPICS Pathfinder calibrated brightness temperatures (radiances) to collocated European Centre for Medium-Range Weather Forecast's Reanalysis v5 (ERA5) data and radiative transfer simulations of Earth's atmosphere using the community radiative transfer model (CRTM). To minimize errors due to radiative transfer uncertainties, we compare TROPICS Pathfinder L1B data from October 2021 with simulated brightness temperature values from the CRTM for observations that are filtered for points near-nadir, over-ocean, free of clouds, and within latitudes from 40 $^°$ N to 40 $^°$ S. We also step through each of the filtering steps individually, to reduce the modeling errors in our comparison. Our results indicate excellent agreement with the simulated brightness temperatures, attaining less than 1 K mean difference between Pathfinder observed radiances and the CRTM simulated radiances for all channels, which is within the 1 K mission requirement.